2018
DOI: 10.1002/jms.4284
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization tandem mass spectrometry of labdane‐type acid diterpenes

Abstract: Copaifera (Leguminoseae) species produce a commercially interesting oleoresin that displays several biological activities, including antimicrobial and anti-inflammatory properties. Labdane-type diterpenes are the main chemical constituents of these oleoresins, and copalic acid is the only compound that has been detected in all Copaifera oleoresins. In this study, we investigate some aspects of the gas-phase fragmentation reactions involved in the formation of the product ions from the deprotonated compounds (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(52 reference statements)
0
14
0
1
Order By: Relevance
“…The identification of casearin‐like compounds is usually performed by high‐performance liquid chromatography with diode‐array detection (HPLC‐DAD) because of the chromophore diene moiety in their side chains ( Z or E , that absorbs in the range of 220 to 235 nm), often assisted by comparison with the retention times of authentic standards, although these are not commercially available 3,21,22 . Similarly, liquid chromatography combined with high‐resolution mass spectrometry (HPLC/HRMS) has assisted the annotation of some diterpenes 23–25 due to its high sensitivity and short analysis times although it is limited for the differentiation of positional isomers 26,27 . Nuclear magnetic resonance (NMR) spectroscopy is a highly effective method for the complete structural elucidation of clerodane‐type diterpenes and differentiation of isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of casearin‐like compounds is usually performed by high‐performance liquid chromatography with diode‐array detection (HPLC‐DAD) because of the chromophore diene moiety in their side chains ( Z or E , that absorbs in the range of 220 to 235 nm), often assisted by comparison with the retention times of authentic standards, although these are not commercially available 3,21,22 . Similarly, liquid chromatography combined with high‐resolution mass spectrometry (HPLC/HRMS) has assisted the annotation of some diterpenes 23–25 due to its high sensitivity and short analysis times although it is limited for the differentiation of positional isomers 26,27 . Nuclear magnetic resonance (NMR) spectroscopy is a highly effective method for the complete structural elucidation of clerodane‐type diterpenes and differentiation of isomers.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing project on the gas‐phase fragmentation reactions of biologically active synthetic and natural compounds, and given the scarcity of ESI‐MS/MS data of MKCs, here we investigate the gas‐phase fragmentation pathways of selected curcuminoids by ESI‐MS/MS combined with thermochemical data obtained at the B3LYP/6‐31+G(d) level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing project on the fragmentation reactions of natural products and synthetic compounds, we investigate the fragmentation pathways of a series of synthetic DBNs and BNs by ESI accurate‐mass MS/MS and MS n combined with thermochemical data estimated by Computational Chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…17 Similarly, Boldizsár and coworkers reported that water elimination from the Cirsium vulgare fruit benzofuran NL balanophonin also involves benzofuran ring opening, with aromatic chain loss followed by aliphatic chain elimination. 18 As part of our ongoing project on the fragmentation reactions of natural products [19][20][21][22][23] and synthetic compounds, 24,25 we investigate the fragmentation pathways of a series of synthetic DBNs and BNs by ESI accurate-mass MS/MS and MS n combined with thermochemical data estimated by Computational Chemistry.…”
mentioning
confidence: 99%